PROBLEMY Z OBSADZENIEM NUNCJATURY W POLSCE (XI 1935 – V 1937) - Łopatecki, Karol (Zeszyty Prawnicze, 2016)
PROBLEMS WITH THE APPOINTMENT OF THE PAPAL NUNCIO TO POLAND, NOVEMBER 1935 – APRIL 1937 Summary The article describes the appointment of Filippo Cortesi to the office of papal nuncio to the Republic of Poland, and reviews the role of the Polish diplomats accredited to the Holy See in this process. The appointment of a nuncio following the departure of Francesco Marmaggi was extremely complicated. The list of candidates was the resultant of a number of factors. The individuals whose names were on it had used influence with the pope, the Vatican’s secretary of state, or former nuncios to Warsaw. Both the Polish government and the bishops of Poland had a say in the final outcome. In addition there was also the volatile political situation in Europe at the time, especially in Spain and Yugoslavia, which exerted an effect on the process. In June 1936 Carlo Chiarlo received the nomination for the office. However, the unanimously negative position of the Conference of the Bishops of Poland, especially Cardinals Kakowski and Hlond, stopped the appointment at the last moment. The Polish Government did not want Ermenegildo Pellegrinetti to be appointed and tried to prevent it, considering Angelo Giuseppe Roncalli the ideal candidate. Eventually Pius XI appointed Filippo Cortesi, formerly nuncio to Argentina.